Challenging Bourdieu's Theory: Dialogic Interaction as a Means to Provide Access to Highbrow Culture for All. (May 2021) - Torras-Gómez, Elisabeth; Ruiz-Eugenio, Laura; Sordé-Martí, Teresa; Duque, Elena
According to Bourdieu, class position is related to cultural capital, taste, and preferences. Accordingly, the author states that, because of their "habitus, " those from high social classes have higher cultural capital and preferences for highbrow culture, which gives them more chances to succeed in life. On the contrary, those from low social classes have lower cultural capital because of their lowbrow cultural preferences, which makes it more difficult for them to achieve in a system that favors the dominant classes. Through the review of articles on Dialogic Literary Gatherings published in peer-reviewed journals, this article aims to provide more insights on how the principles of dialogic learning occur. The results of the review challenge Bourdieu's concept of "habitus, " providing evidence of how socioeconomic status (SES) is not determinant to cultural capital.